If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y = cos(x + -1)(x + 1) Reorder the terms: Y = cos(-1 + x)(x + 1) Reorder the terms: Y = cos(-1 + x)(1 + x) Multiply (-1 + x) * (1 + x) Y = cos(-1(1 + x) + x(1 + x)) Y = cos((1 * -1 + x * -1) + x(1 + x)) Y = cos((-1 + -1x) + x(1 + x)) Y = cos(-1 + -1x + (1 * x + x * x)) Y = cos(-1 + -1x + (1x + x2)) Combine like terms: -1x + 1x = 0 Y = cos(-1 + 0 + x2) Y = cos(-1 + x2) Y = (-1 * cos + x2 * cos) Y = (-1cos + cosx2) Solving Y = -1cos + cosx2 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Simplifying Y = -1cos + cosx2
| 4e^7t=9e^6t | | 5/2=6-2/4 | | 3x^2+28x-240=0 | | 3x-33=-4x+58 | | 2(x-1)=7x-7-5x | | 4x^2+28x-240=0 | | 38-n=34 | | (4n-15)= | | x/3-4x | | -2x^2+12=-3x^2+7x | | y=-.33x^2+1.5x+0 | | (7x+3)(4x-5)= | | 100-c=129 | | 2d-4(d+6)=6d-48 | | (5a^2b-^3/10a-^2b-^4)^3 | | z/5-4=3/1/3 | | .15x+20=.10x+30 | | .10x+.25y=5.10 | | 9x18/5 | | 9.2x+50.82=-10.8x+50.10 | | (5a^2b-^3)/(10a-^2b-^4)^3 | | 9x+3=65 | | K+(4K+32)=32 | | 20-x/15=17 | | 4(2x-8)+6=26 | | 250000=5000{[(1.12)^n-1]/[.12]} | | 5w+10=15w | | 57x=45 | | 4(w-16)+2w=0 | | 4x=9x-9 | | 4m-7=1 | | 4x+ef=9x-9 |